MEMBUMIKAN PEMIKIRAN ISLAM PROGRESSIF ALA ABDULLAH SAEED - Fathiyaturrahmah (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2014)
The progress of information technology and communication have made this world become increasingly global. Now many problems that previously only develops in the west has become global issues, in which no one was a muslim country that can prevent away from involvement with issues surrounding democracy, human rights, gender equality, and religious pluralism is a global trend that could not not to be responded to by muslims as part of global humanitarian. Because of it , Saeed Abdullah as intellectual or mujtahid of the muslim minority living in the new world , in the region the majority of non-muslims, provide solutions how spirit of the teachings of Islam that can identified as “sholihun li kulli makanin wa zamanin”. Spirit of a kind of this is what he called with progressive Islam, the subject known as progressive muslim, efforts to turn back the progressive dimension of Islam that in the last long enough brain dead were suppressed by the dominance of the text. Think the method used by muslim progressive this is what he called with the term progressive ijtihadi trend is one of contemporary Islamic thought continually that contexted the text in accordance with the condition and desire to answer the needs as human beings.